Taur-Taur Simbandar: Analisis Nilai-nilai Pendidikan dan Relevansinya di Era Digital - Tesalonica Evelin Br Sitorus; Chintiah Lafaezah Sihaloho; Filomena Nova Julianti Sinurat; Kezia Tarila Rubina Sitepu; Tri Indah Prasasti (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the educational values ​​contained in Taur-Taur Simbandar and its relevance in the digital era. Taur-Taur Simbandar is an oral tradition of the Simalungun people in the form of a reciprocal dialogue between garama and anak boru containing moral, social, and cultural messages. This study uses a descriptive qualitative approach with data sources in the form of a transcription of the Taur-Taur Simbandar text. Data were collected through literature and documentation studies, then analyzed using content analysis techniques by paying attention to the structure of the dialogue, choice of diction, symbolic repetition, and the cultural context of the Simalungun people. The results show that the educational values ​​in Taur-Taur Simbandar are not only conveyed explicitly through the lyrics, but are also built through patterns of reciprocal communication between characters. The values ​​of honesty and responsibility emerge through the affirmation of trust and loyalty in the dialogue, while the values ​​of communicativeness and peace are reflected through responses that maintain harmonious relationships. In addition, the value of independence is represented through the symbol of wandering as a form of readiness to face life. These findings indicate that Taur-Taur Simbandar serves as a character education medium based on local wisdom that remains relevant in fostering critical, ethical, and responsible attitudes in the digital age.